The impact of COVID-19 and strategies for mitigation and suppression in low- and middle-income countries - Walker,PGT; Whittaker,C; Watson,OJ; Baguelin,M; Winskill,P; Hamlet,A; Djafaara,BA; Cucunubá,Z; Olivera,Mesa D; Green,W; Thompson,H; Nayagam,S; et al. (Science, 2020)
The ongoing COVID-19 pandemic poses a severe threat to public health worldwide. We combine data on demography, contact patterns, disease severity, and health care capacity and quality to understand its impact and inform strategies for its control. Younger populations in lower income countries may reduce overall risk but limited health system capacity coupled with closer inter-generational contact largely negates this benefit. Mitigation strategies that slow but do not interrupt transmission will still lead to COVID-19 epidemics rapidly overwhelming health systems, with substantial excess deaths in lower income countries due to the poorer health care available. Of countries that have undertaken suppression to date, lower income countries have acted earlier. However, this will need to be maintained or triggered more frequently in these settings to keep below available health capacity, with associated detrimental consequences for the wider health, well-being and economies of these countries.